REALIZACJA ZASADY SPRAWIEDLIWOŚCI W KARANIU PRZESTĘPCÓW - Niewiadomska, Iwona; Fel, Stanisław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article consists of three parts. The first describes the essence of the principle of justice, especially in the context of the function that it plays in regulating social life. The second part of the article shows how to implement principles of justice under Polish penal law. In this context, justice is shown to be one of the four main objectives for punishing criminals (besides general preventive, particular preventive and compensational objectives). The third part of the article presents the multidimensional consequences of a sense of injustice in the convicted criminals. The analysis of this issue is presented in two respects: punishing by imposing isolation sanctions and the psychological consequences of penitentiary isolation and the social consequences of enduring a penalty of imprisonment.